Implementasi Smart Tourism Melalui Digitalisasi Informasi Homestay dan Produk Unggulan Desa Sawarna Berbasis Web - Ahmad Fathurrozi; Tri Ginanjar Laksana; Anis Athifah; Arya Haifandika; Arya Radithya; Ayu Diah Rositawati; Christoba Parulian Sihombing; Hafidz Maulana Rahman; Muhammad Reza Alfarizki; Muhammad Fathan Zulkarnain; Nur Aziz Raihan; Seychar Ramadhan; Wahyu Triyanto (Journal Of Computer Science Contributions (JUCOSCO), 2025)
This program aims to implement the concept of Smart Tourism through the digitization of homestay information and leading products of Sawarna Village using a web-based platform. Digitizing information facilitates access to data related to accommodation, facilities, prices, and village specialty products, thereby increasing visibility and tourism and supporting the promotion of tourism and local MSMEs. The implementation method involves platform development, field data collection, and training for the community and village officials in information management. The results show an increase in information access, digital literacy, and community participation in tourism development. This program has a positive impact on local economic growth and increases the professionalism of KKN students.